Tren Bisnis Tour Ke Tiongkok - Citra Ayu Novitasari; Panca Nugraha (Jurnal Pariwisata Terapan, 2017)
In recent years, several cities in Indonesia have been rife with the business tour to China. The purpose of this business tour is to survey and analyze wholesale market and factories in China. The cheap goods from China is the main reason for the beginners and mid-sized businesman, online and offline begin to try to follow this tour. The number of enthusiasts makes more and more individual or tour agent who offer services for tour business assistance to China. This is a new opportunity for tour and travel business in Indonesia. The purpose of this study is to know the trend of tourism business or business tour in Indonesia today.